2014
DOI: 10.5194/cp-10-1843-2014
|View full text |Cite
|
Sign up to set email alerts
|

Water pH and temperature in Lake Biwa from MBT'/CBT indices during the last 280 000 years

Abstract: Abstract. We generated a 280 000 yr record of water pH and temperature in Lake Biwa, central Japan, by analysing the methylation index (MBT ) and cyclisation ratio (CBT) of branched tetraethers in sediments from piston and borehole cores. Our aim was to understand the responses of precipitation and air temperature in central Japan to the East Asian monsoon variability on orbital timescales. Because the water pH in Lake Biwa is determined by phosphorus and alkali cation inputs, the record of water pH should ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Copyright # 2016 John Wiley & Sons, Ltd. season of brGDGTs in temperate lakes. Applying a reconstruction restricted to MST might thus result in missing potential in situ bio-production during other times of the year and it also needs to be considered that brGDGTs from paleo-records comprise a mixed signal over longer time periods less specific to seasonal growth periods (Schoon et al, 2013;Ajioka et al, 2014). However, in regimes with a long period of ice cover on lakes, such as in the Arctic or Antarctic, microbial productivity is shifted to the summer season and hence in such cases summer temperature should be preferred for correlation (e.g.…”
Section: Lake Sediments à Mbt M and Mbt Calibrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright # 2016 John Wiley & Sons, Ltd. season of brGDGTs in temperate lakes. Applying a reconstruction restricted to MST might thus result in missing potential in situ bio-production during other times of the year and it also needs to be considered that brGDGTs from paleo-records comprise a mixed signal over longer time periods less specific to seasonal growth periods (Schoon et al, 2013;Ajioka et al, 2014). However, in regimes with a long period of ice cover on lakes, such as in the Arctic or Antarctic, microbial productivity is shifted to the summer season and hence in such cases summer temperature should be preferred for correlation (e.g.…”
Section: Lake Sediments à Mbt M and Mbt Calibrationsmentioning
confidence: 99%
“…These authors subsequently proposed that the methylation index of branched tetraethers (MBT) and cyclization index of branched tetraethers (CBT) together enable the reconstruction of mean annual air temperature (MAT) in terrestrial environments such as soils and peat bogs. As brGDGTs also occur ubiquitously in lake sediments, the MBT/CBT index has been used to determine variation in continental climates in several paleoenvironmental studies (Tierney and Russell, 2009;Tierney et al, 2010;Pearson et al, 2011;Loomis et al, 2012;Niemann et al, 2012;Ajioka et al, 2014;Colcord et al, 2015). Many of those studies, however, have shown that the application of temperature calibrations derived from the distribution of brGDGTs in soils generally results in reconstructed MAT values that underestimate actual temperature trends.…”
Section: Introductionmentioning
confidence: 99%
“…Given the temperature and pH dependence of brGDGT indices in soils and peats, they are used as proxies for these parameters in loess-palaeosol, peat and sedimentary records (e.g. Weijers et al, 2007;Schouten et al, 2008;Rueda et al, 2009;Ballantyne et al, 2010;Bendle et al, 2010;Tyler et al, 2010;Fawcett et al, 2011;Peterse et al, 2011;Gao et al, 2012;Niemann et al, 2012;Zech et al, 2012;Ajioka et al, 2014b;Sanchi et al, 2014;Cao et al, 2017;Wang et al, 2017a). However, brGDGTs are also argued to be produced in situ within the water column or the sediments of aquatic settings (e.g.…”
Section: Introductionmentioning
confidence: 99%